Characteristic metabolite profile of 10 colorectal cancer-related bacteria - Liu, Yongqiang; Mei, Wangli; Huang, Xinyan; Yao, Xudong; Kong, Cheng; Chen, Yifan (Frontiers in Oncology, 2025)
BackgroundTumor metabolomics of colorectal cancer (CRC) is significantly different from normal tissues, due to nutrient deprivation, metabolite accumulation, acidity and hypoxia. Besides, gut microbiota has been confirmed to affect the progression of CRC. Microbiota metabolites might participate in the metabolic reprogramming of CRC cells and further regulate tumor microenvironment.Method10 CRC-related strains are cultured in vitro (10 replicates per bacterium), including Enterotoxic Escherichia coli (ETEC), Peptostreptococcus anaerobius (Pa), Fusobacterium necroporum (Fne), Fusobacterium nucleatum (Fn), Lactobacillus plantarum (Lp), Lactobacillus acidophilus (La), Lactobacillus casei (Lc), Lactobacillus rhamnosus gg (LGG), Bifidobacterium bifidum (Bbi), Bifidobacterium Breve (Bbr). Bacterial culture supernatant is subjected to gas chromatography-mass spectrometry.ResultThe 10 CRC-related strains have characteristic metabolite profiles, mainly referring to specific saccharides, amino acids, bile acids, polyamines and bioactive compounds. Saccharides and organic acids increase significantly in Lactobacillus (Lp, LA, Lc and LGG) compared with culture medium and other strains, such as galactinol, 1-ketose, beta-gentiobiose, glutaric acid, 3-phenyllactic acid, indlol-3-lactate. Chlorogenic acid, a beneficial polyphenol, increases significantly in Bbr. The abundance of amino acids and their derivatives changes significantly in Bifidobacterium (Bbi and Bbr), such as 2-hydroxy-2-methylbutanoic acid, N-acetyl-5-hydroxytryptamine and glutamate. Bile acids (lithocholic acid and cholic acid), polyamine (spermine), amino acids and derivatives (N-acetylaspartate, glutamate) increased significantly in the CRC-related pathogens (ETEC, Pa, Fn and Fne). Correspondingly, metabolic pathways are significantly affected, mainly including amino acid metabolism and nucleotide metabolism.ConclusionThe 10 CRC-related strains possess significantly different metabolites and metabolic pathways. Specific metabolites and corresponding metabolic pathways might explain microbial CRC-promoting or -suppressing mechanisms.